KOMUNIKASI ORGANISASI DI SEKTOR PEMBANGKIT LISTRIK ASAM ASAM (Studi Kasus pada Unit Pelaksana Bagian Enjiniring PLTU Asam Asam) - Ika Utami; Gusti Irhamni (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
This study aims to describe the communication that exists in Asam Asam Coal Steam Power Plant Engineering Department, identifying problems in organizational communication, then prepare recommendations to improve the condition of organizational communication based on existing communication theory. The method in this research is descriptive with qualitative approach. Data are collected through observation, documentation, and in-depth interviews of engineering department leaders, predictive maintenance staff, system management staff, and information technology staff. The results showed that organizational communication which is not running well implicates the performance of staff in achieving the vision and mission of the organization. The openness in vertical communication is one of the main factors affecting the effectiveness and climate of communication in achieving the vision and mission of the organization. Furthermore, to support the coordination function of Engineering Department, the structural position as supervisor is considered necessary as a command chain from Assistant Manager to subordinates in each division. Keywords: Management, Communication and Producer